Analisis Yuridis Perlindungan Hukum Bagi Korban Salah Tangkap Ditinjau Dari Ketentuan Hukum Positif Di Indonesia - Setyawan, Gerald Febrian; Prasetyo, Boedi (LPPM STAI Muhammadiyah Probolinggo, 2025)
The judicial process in Indonesia must be carried out or implemented based on the provisions of the laws in Indonesia. The criminal justice process was born in order to resolve problems that arise from criminal acts. Although the procedures for the judicial process have been regulated by law, we still find many cases of errors in the judicial process that occur in Indonesia. One case of error in the judicial process can be found in cases of mistaken arrest by law enforcement officers. Wrongful arrests or mistakes in arrest generally occur due to procedural errors and also errors in the investigation process carried out by law enforcement officers. In order to protect the interests and rights of victims that are lost during the judicial process, a form of protection is needed that can be given to victims of mistaken arrest. Legal protection for victims of mistaken arrest was born in order to provide protection for victims or innocent people who were arrested illegally or mistakenly by law enforcement officers. Including provisions for victim protection aims to increase the government's focus on the plight of victims and can restore the conditions and rights of victims that are lost from the act of mistaken arrest considering that the act of mistaken arrest is a form of gross human rights violation that greatly tarnishes human dignity